Point and counterpoint in the Institutional Evaluation: documents analysis of the establishment of SINAES. - José Carlos Rothen (Educação: Teoria e Prática, 2007)
Taking as presupposition that the history of the institutions evaluation follows two directions, that are emancipation/formation and regulation/control, this work has as investigation object the documents produced in the scope of the Ministry of Education that established SINAES, in order to identify their evaluation conceptions. In a first moment in order to contextualize the debate, we present a brief historical reconstitution of the processes of institutional evaluation. For that, the two evaluation types mentioned above will be used as leading elements. Secondly, the documents on the evaluation which are produced by the National Commission of Evaluation of the Higher Education (CONAES)/INEP are analyzed, as well as the proposal of MEC of ordinance that links the evaluation and the regulation. It is concluded that the impasse of Lula’s government in defining the function of the evaluation, makes it difficult to establish SINAES. The delay in the definition of what and how to evaluate might suggest that the government does not get to accomplish a complete cycle of the institutional evaluation.